Features of modern light industry of developing countries in global competition - Ukubassova, G.S.; Galiyeva, A.Kh.; Kozhabayeva, S.A.; Amirbekova, A. (BUKETOV BUSINESS REVIEW, 2019)
In the article the features of the development of light industry sector in the consideration of the emergence in global market are discussed. The features of light industry are the insignificant need for capital investments, constant growth, rapid capital turnover. Therefore, this industry has become the starting point in the economics of developed countries, and in developing countries it is considered with high priority. This paper presents the experience of the development of light industry in China, Turkey and Kyrgyzstan, where there is a constant increase due to the steady increase in demand for products. Through the implementation of a wellthought-out strategy covering the macro, industry and micro level, the success of light industry development has been achieved in most countries. Light industry as an industry is a set of enterprises, producing goods that compete with each other and meet similar needs. The demand for light industry products is constantly growing. Buyers increasingly prefer high-quality goods, although in the recent yeas price was the determining factor when choosing a product. Light industry is a powerful diversified complex, both in the production of consumer and industrial goods, and carries out both the primary processing of raw materials and the production of finished products.